Potassium(I) amidotrihydroborate: structure and hydrogen release. - Diyabalanage, H; Nakagawa, T; Shrestha, R; Semelsberger, T; Davis, B; Scott, B; Burrell, A; David, W; Ryan, K; Jones, M; Edwards, P (2010)
Potassium(I) amidotrihydroborate (KNH(2)BH(3)) is a newly developed potential hydrogen storage material representing a completely different structural motif within the alkali metal amidotrihydroborate group. Evolution of 6.5 wt % hydrogen starting at temperatures as low as 80 degrees C is observed and shows a significant change in the hydrogen release profile, as compared to the corresponding lithium and sodium compounds. Here we describe the synthesis, structure, and hydrogen release characteristics of KNH(2)BH(3).